2016
DOI: 10.1109/tkde.2016.2554119
|View full text |Cite
|
Sign up to set email alerts
|

GenPerm: A Unified Method for Detecting Non-Overlapping and Overlapping Communities

Abstract: Abstract-Detection of non-overlapping and overlapping communities are essentially the same problem. However, current algorithms focus either on finding overlapping or non-overlapping communities. We present a generalized framework that can identify both non-overlapping and overlapping communities, without any prior input about the network or its community distribution. To do so, we introduce a vertexbased metric, GenPerm, that quantifies by how much a vertex belongs to each of its constituent communities. Our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 45 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Although there have been many studies in overlapping community detection so far, the complexity and accuracy of existing overlapping community detection algorithms still need to be improved. erefore, it is necessary to study the detection of overlapping communities [24].…”
Section: Overlapping Community Detectionmentioning
confidence: 99%
“…Although there have been many studies in overlapping community detection so far, the complexity and accuracy of existing overlapping community detection algorithms still need to be improved. erefore, it is necessary to study the detection of overlapping communities [24].…”
Section: Overlapping Community Detectionmentioning
confidence: 99%
“…Most optimization metrics consider the total number of external neighbors of the vertex. However, in our earlier experiment [Chakraborty et al 2014;Chakraborty 2015;Chakraborty et al 2016b], we empirically demonstrated that a group of vertices are likely to be placed together so long as the number of internal connections is larger than the number of connections to any one single external community. In other words, a vertex which has connections to some external communities, experiences a separate "pull" from each of these external communities.…”
Section: Defining Permanencementioning
confidence: 95%
“…Composite Performance: Figure 4(c) shows performance of all classifiers on families of size ≥ 10 considering both static and dynamic features. For better visualization we adopt the setup used in [25] -for each evaluation metric (such as MiF, MaF, MiAUC, MaAUC), we separately scale the scores of the methods so that the best performing method has a score of 1. The composite performance of a method is the sum of the four normalized scores.…”
Section: Performance Analysismentioning
confidence: 99%